MEMBANGUN SEMANGAT WIRAUSAHA DI KALANGAN GEN-Z BAGI MAHASISWA UNIVERSITAS HORIZON INDONESIA - Aliman, Aliman - (Divisi Pengabdian dan Pemberdayaan Masyarakat (DP2M) UNIKOM, 2025)
There are many opportunities for Generation Z or GenZ to succeed as a businessman or entrepreneur. However, they still need guidance and instruction, to acquire essential skills, boost, and entrepreneurial spirit. Therefore, this entrepreneurship seminar is one way or solution that can be done. The implementation of this entrepreneurship seminar can influence the ability of participants in the basic insights to start an entrepreneur, as well as understanding the mental mindset required when starting to become an enterprise. It is known that the entrepreneurial seminar is the first program designed to enhance the knowledge, attitude, and entrepreneural skills that fit the Generation Z model. Thus, it can be the starting capital for participants to start a business while developing an existing enterprise and becoming a successful businessman.